Analysis of the 3D microstructure of tape-cast open-porous materials via a combination of experiments and modeling. (5th November 2017) - Haj Ibrahim, S.; Neumann, M.; Klingner, F.; Schmidt, V.; Wejrzanowski, T.
Abstract: In the present paper, fabrication, characterization and modeling techniques are combined to analyze the microstructure of tape-cast open-porous materials. This kind of material is highly permeable to gases and at the same time has a high catalytic reactivity which leads to successful applications e.g. in high-temperature fuel cells. However, the microstructure of such material is complex and not fully understood. The main goal of this paper is to provide a realistic model of tape-cast porous microstructures based on the simulation of their fabrication process. In order to accomplish this, four different samples are fabricated by firing the green tapes obtained by the tape casting process. The microstructure of each sample is analyzed by means of micro-tomographic image data. Furthermore, a method for modeling open-porous 3D microstructures is proposed, where the cast slurry is represented by a system of spheres with a given volume fraction and radius distribution. Model-based post-processing of the simulated microstructures is proposed to improve the fit of the surface area. Finally, model validation is performed by means of a detailed statistical analysis of experimentally produced and virtual microstructures. Graphical abstract: Highlights: Open-porous nickel-based materials with various amounts of porogen were fabricated by a tape casting and firing procedure. 3D microstructures of the manufactured materials were analyzed by X-ray tomography. A novel 3D model of tape-cast porous microstructures based on the simulation of their fabrication process was developed. Model validation was performed by utilizing statistical analysis of both 3D model structures and tomography images. A good representation of porous structure was obtained in terms of porosity, mean pore size and tortuosity.